Mechanisms Underlying Sexual Violence Exposure and Psychosocial Sequelae: A Theoretical and Empirical Review - Walsh, Kate (Clin Psychol (New York), 2012)
Sexual violence is associated with a range of negative mental health and behavioral sequelae, including posttraumatic stress disorder (PTSD), depression, substance abuse/dependence, risky sexual behavior, and interpersonal relationship problems. However, mechanisms underlying these associations are not well understood. Identifying mechanisms that explain linkages between sexual violence and poor outcomes is of paramount importance in determining when and how to intervene to prevent or reduce the magnitude of these outcomes. This review focuses on theories that have been proposed to explain risk of negative outcomes among sexual violence victims, including the development of traumagenic dynamics and emotion dysregulation. We also review promising biological mechanisms that may explain the risk of negative outcomes among sexual violence victims, including studies concerned with epigenetic and neurobiological mechanisms.